Exopolysaccharide producing bacteria of Sundarban Mangrove Forest soil and their antibiotic sensitivity profile - Zennathara; Afrin, Sadia; Ali, Mohammad; Islam, Mohammad Nurul; Saha, Mihir Lal (Dhaka University Journal of Biological Sciences, 2023)
This study focused on the investigation of Exopolysaccharide (EPS) producing bacteria from Sundarbans mangrove forest (SMF) soil, Bangladesh. The heterotrophic bacterial loads in the soil samples varied from 0.44×107 to 4.2×107 cfu/g indicating high bacterial load even under hostile environment. Fifteen EPS producing bacterial isolates were identified provisionally where thirteen isolates belonged to the genus Bacillus including B. badius (n=1, 6.67%), B. subtilis (n=3, 20.0%), B. pumilus (n=3, 20.0%), B. brevis (n=2, 13.33%), B. stearothermophilus (n=2, 13.33%), B. sphaericus (n=1, 6.67%) and B. alcalophilus (n=1, 6.67%). The remaining two isolates were recognized as the genus Micrococcus sp. (n=2, 13.33%). The genus Bacillus was predominant representing 86.67% abundance frequency. The LB medium was proven to be the most suitable medium for the growth of EPS producing bacterial isolates. 16S rDNA sequence analysis was conducted for three EPS producing bacterial isolates and they were identified as Bacillus subtilis, B. strearothermophilus and Micrococcus sp. The antibiogram profile of this study revealed streptomycin as the most effective antibiotic to control the growth of bacteria. The presence of antibiotic resistance bacteria in SMF soil is alarming for human health associated with this marine ecosystem. The multidrug resistance bacteria may come to the soil of SMF through the untreated discharged wastewaters and agricultural runoff from adjacent areas. Dhaka Univ. J. Biol. Sci. 32(2): 243-255, 2023 (July)